Statistical Analysis of Randomly Oriented Strands (ROS) of Thermoplastic Composite Materials - Isguzar, T.; Eker, A. Akdogan; Dogu, M. (SPRINGER, 2025)
Recently, randomly oriented strands (ROS) have found widespread use in the production of complex thermoplastic composite parts; however, these materials suffer from a significant disadvantage. During the production of parts using this material, voids occur due to the overlapping of strands. This study focuses on statistical analysis of the strength variations in ROS composites. Materials made from the strands of two different lengths were tested in tension and the strength's reliability was assessed implementing Weibull analysis. Composite strands were produced from a unidirectional glass fiber-reinforced polypropylene (GF/PP) prepreg. The tension test results showed that the specimens with longer strands possess higher tensile strength than those with shorter strands. The wide range of variation in the tension test results can be attributed to both the presence of voids in the material and the randomness in strand orientation. Tension test values at 90% reliability in the Weibull distribution were considerably lower than the average test values.
Keywords: randomly oriented strands (ROS); Weibull distributions; thermoplastic composites; glass fiber-reinforced polypropylene prepreg; MECHANICAL-PROPERTIES; Mechanics; Materials Science; Polymer Science